The Prediction of the Electromagnetic Properties and the ?(E2/M1) of 110-116Cd-Isotopes in IBM Model (Baghdad Science Journal, 2011)
The Nuclear structure of 110-116Cd isotopes was studied theoretically in the framework of the interacting boson model of IBM-l and IBM-2. The properties of the lowest mixed symmetry states such as the 1+, 2+ and 3+ levels produced by the IBM-2 model in the vibrational-limit U(5) of Cd - isotopes are studied in details. This analysis shows that the character of mixed symmetry of 2+ is shared between and states in 110-114Cd – isotopes, the large shar goes to s, while in isotope, the state is declared as a mixed symmetry state without sharing. This identification is confirmed by the percentage of F-spin contribution. The electromagnetic properties of E2 and Ml operators were investigated and the results were analyzed. Various values of eB in the IBM-l and fixed e?= 0.104 eb and e?=0.093 e.b in the IBM-2 are used to generate the B(E2) and Q(2+). Fixed values of g? =0.31?N and g? =-0.31?N were adopted to generate the B(Ml) and ?(E2/ Ml) mixing ratios. The small values of ?(E2/Ml) which obtained for transition from MS- states to those of full symmetry support the conclusion that there may be a strong Ml transition between these states.